Effects of Private Tutoring on English Performance: Evidence from Senior High Students in Taiwan - Chih-Hao, Chang (International Journal of Educational Development, 2019)
Private tutoring has expanded as a global phenomenon and is receiving increasing research attention, but evaluation studies on private tutoring are lacking. By performing a control-group pretest-posttest experiment, this study examined the effectiveness of English private tutoring (EPT) on the academic performance of Taiwanese secondary school learners. One group of students (N = 100) participated in EPT for three months and was compared to a non-tutored control group (N = 100). Using national college entrance exam data gathered in 2017 and 2018 and t-tests and difference-in-differences (DID) analysis, the present study found that differences in the effect of EPT on students’ academic performance between the tutored and non-tutored groups decreased in magnitude after considering the students’ individual characteristics, family socioeconomic status, school type, and self-study practices. Among these variables, the time students spent on self-study activities had a more significant positive effect than did private tutoring. The findings from this study show that as an alternative to investing in EPT, investing time and effort in self-study activities can lead to an increase in students’ academic performance. These data from Taiwan contribute to the international analysis on private tutoring and add an important component to the broader conceptual literature.
Keywords: Aspects économiques de l'éducation